Analisis Hubungan antara Pemilik Kebun, Pekerja dan Tengkulak dalam Budidaya Rumput Taman Desa Kidangbang, Kecamatan Wajak, Kabupaten Malang - Chusnul Chotimah; Intan Ronna Zulia Citta Dhewi; Ahnanursiami (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Brawijaya, 2024)
Kidangbang is a village in Malang that has cultivation for garden grass run by the majorityof the villagers. They are not selling the grass directly to the market, but they sell it to thewholesaler. There are some parties that run the business. They are land owners, workers, and thewholesaler. This research aims to understanding the relationship between them. The objective here isto describe the relationship between the land owners, workers, and the wholesaler. This research wasconducted in Kidangbang village, Wajak district, Malang Regency. Data are collected by conductingPRA (Participatory Rural Appraisal) multi mapping analyzed with venn diagram and swot analysis.The result shows that the relationship between them occurs by trust and network that associates thegood business relationship at the garden grass cultivation until now. Good relationships that areformed also affect the conditions of the surrounding environment. The interaction that exists betweenactors also plays a role in environmental conservation efforts, by protecting and preserving nature. Keywords: relations, embeddedness, vilage